Cornus officinalis: a potential herb for treatment of osteoporosis - Tang, Xinyun; Huang, Yuxin; Fang, Xuliang; Tong, Xuanying; Yu, Qian; Zheng, Wenbiao; Fu, Fangda (Frontiers in Medicine, 2023)
Osteoporosis (OP) is a systemic metabolic skeletal disorder characterized by a decline in bone mass, bone mineral density, and deterioration of bone microstructure. It is prevalent among the elderly, particularly postmenopausal women, and poses a substantial burden to patients and society due to the high incidence of fragility fractures. Kidney-tonifying Traditional Chinese medicine (TCM) has long been utilized for OP prevention and treatment. In contrast to conventional approaches such as hormone replacement therapy, TCM offers distinct advantages such as minimal side effects, low toxicity, excellent tolerability, and suitability for long-term administration. Extensive experimental evidence supports the efficacy of kidney-tonifying TCM, exemplified by formulations based on the renowned herb Cornus officinalis and its bioactive constituents, including morroniside, sweroside, flavonol kaempferol, Cornuside I, in OP treatment. In this review, we provide a comprehensive elucidation of the underlying pathological principles governing OP, with particular emphasis on bone marrow mesenchymal stem cells, the homeostasis of osteogenic and osteoclastic, and the regulation of vascular and immune systems, all of which critically influence bone homeostasis. Furthermore, the therapeutic mechanisms of Cornus officinalis-based TCM formulations and Cornus officinalis-derived active constituents are discussed. In conclusion, this review aims to enhance understanding of the pharmacological mechanisms responsible for the anti-OP effects of kidney-tonifying TCM, specifically focusing on Cornus officinalis, and seeks to explore more efficacious and safer treatment strategies for OP.